Cigarette filter butts-derived activated carbon with free binder electrode design for solid-state supercapacitor application - Faridah Lisa Supian (Tanjung Malim, 2023)
Cigarette filter butts-derived activated carbon with free binder electrode design for solid-state supercapacitor application by Faridah Lisa Supian